Always time to die - Lowell, Elizabeth, 1944- (Avon, 2006)
Hired by the eccentric aunt of New Mexico's multimillionaire governor Quintrell to research their family, genealogist Carolina May stumbles into a dark and dangerous secret about the Quintrell family that threatens her life.